Pole Teppo Wara: Strategi Bertahan Hidup Masyarakat Nelayan Pancing Pada Musim Paceklik di Pulau Kerasian - Muhammad Fadli Junaedi; Arif Rahman Hakim (Huma: Jurnal Sosiologi, 2023)
The fishing rod fishing community of Kerasian Island Village depends on the utilization of marine resources and is very dependent on the season, so that when the famine season arrives they find it difficult to find sources of income which has an impact on the family's economic condition. This study aims to find out and describe how the survival strategy of fishing rod communities in facing the famine season in Pulau Kerasian Village with an ethical theory approach to subcessence. The research method used is qualitative with a descriptive approach. The determination of informants in this study was by Purposieve Samling. The research informant was a family of fishing rod fishermen. The results showed: (1) minimizing family expenses is part of the survival strategy carried out by fishing families in Pulau Kerasian Village by implementing frugal living and replacing food of lower quality; (2) diversification of fishing workers during the famine season in Pulau Kerasian Village is mala'du or fishing not far from the plains, changing fishing areas, chart fishermen, boatbuilders, and the involvement of family members; (3) Good social relations are a solution for fishing families in Pulau Kerasian Village to survive when the famine season arrives by asking for help from their relatives, be it help from family, debt to neighbors, and assistance from the government. The study concluded that fishing rod fishermen in Pulau Kerasian Village have various strategies to survive in the face of famine seasons that occur every year.